If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13t + 12 = 19t Reorder the terms: 12 + 13t = 19t Solving 12 + 13t = 19t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-19t' to each side of the equation. 12 + 13t + -19t = 19t + -19t Combine like terms: 13t + -19t = -6t 12 + -6t = 19t + -19t Combine like terms: 19t + -19t = 0 12 + -6t = 0 Add '-12' to each side of the equation. 12 + -12 + -6t = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -6t = 0 + -12 -6t = 0 + -12 Combine like terms: 0 + -12 = -12 -6t = -12 Divide each side by '-6'. t = 2 Simplifying t = 2
| 3xsquared+4=40 | | s-1/4=4/8 | | z-9=2z-41 | | x^2/8-1/x | | 12z-46=98 | | 8m^2=-3m | | 27x^2=0 | | 100-y=81 | | -7x+5=x-2 | | 8(k+3)=2x+(-4) | | x-(-9)=-12 | | 3y-78=y-10 | | 14-x=z | | 2916=x(x)(0.5x) | | 52=47+x | | 12x+25=7x+25 | | 8x-30-3x=2(x+5)+8 | | X+70+65=180 | | 11x=3x+4 | | 2a+1=3a-2 | | 5/9*9/5C5/9*56 | | 5/9•9/5C5/9•56 | | 7z-42=4z | | 5y+6y+8y-12y+30= | | -2(m-20)=-6m | | 4/3x3.14x8^3 | | 1-9/x^2=0 | | 19s-64=8s-9 | | 11x-60=x | | 1-9/x^2 | | x^3+10x^2-8=0 | | 3x^2-16x-30=0 |